Ignatian Spirituality and Action Research: Exploring Lay Ecclesial Ministerial Formation - Ross, Deborah (The way, 2022)
The article discusses a combination of action research and Ignatian spirituality to assess its practice of lay ecclesial ministerial formation in the Jesuit School of Theology in California. The precepts of Ignatian spirituality guided the action research process in a prayerful and mission-orientated practice of institutional discernment. The project helped to take notice of the movements of God's spirit within the school, endowing the process with an incarnational quality.